2013
DOI: 10.1163/15685381-00002904
|View full text |Cite
|
Sign up to set email alerts
|

Genome dosage effect and colouration features in hybridogenetic water frogs of the Pelophylax esculentus complex

Abstract: There are three taxons of central European water frogs of the Pelophylax esculentus complex: two morphologically distinct species, Pelophylax lessonae (LL) and Pelophylax ridibundus (RR), and hybrids Pelophylax esculentus, which can be either diploid (RL) or triploid (LLR or RRL). The morphology of hybrids is supposed to follow genome dosage effect. We describe colouration of water frogs with genome composition verified by chromosome analysis. Typical colouration features in LL were: spots on the ventral side,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…In central and southern populations, when comparing the AA genomotype with the distinct hybrid combinations (PA, PAA and PPA) and with the pure PP ( S. pyrenaicus ), only the extreme genomotypes are identifiable with confidence. Such patterns seem to result from a dosage effect of parental genome contributions [see also Kierzkowski et al, 2011] and are particularly visible regarding the number of scales (slightly higher in AA, when compared with the PP extreme), number and size of gill rakers (higher in AA), position of the mouth (more terminal in AA), and body coloration. The latter of which, in AA individuals, includes a clearly visible longitudinal dark stripe that is lighter in the hybrid genomes and nonexistent in S. pyrenaicus [reviewed in Collares-Pereira and Coelho, 2010].…”
Section: Biology and Ecologymentioning
confidence: 99%
“…In central and southern populations, when comparing the AA genomotype with the distinct hybrid combinations (PA, PAA and PPA) and with the pure PP ( S. pyrenaicus ), only the extreme genomotypes are identifiable with confidence. Such patterns seem to result from a dosage effect of parental genome contributions [see also Kierzkowski et al, 2011] and are particularly visible regarding the number of scales (slightly higher in AA, when compared with the PP extreme), number and size of gill rakers (higher in AA), position of the mouth (more terminal in AA), and body coloration. The latter of which, in AA individuals, includes a clearly visible longitudinal dark stripe that is lighter in the hybrid genomes and nonexistent in S. pyrenaicus [reviewed in Collares-Pereira and Coelho, 2010].…”
Section: Biology and Ecologymentioning
confidence: 99%
“…The difficulty of establishing a close correspondence between geno- typic composition and external morphology of green frogs is likely due to the high morphological variability of these species (Hotz and Bruno, 1980;Gubányi and Korsos, 1992;Gün-ther and Plötner, 1994;Lode and Pagano, 2000). A number of papers have focused on the identification and characterization of genetic variability, DNA contents, and genomic composition of RanalPelophyiax hybrids and their parental forms (Uzzell and Hotz, 1979;Ragghianti et al, 1995Ragghianti et al, , 2007Bucci et al, 2000;Ogielska, Kierzkowski and Rybacki, 2004;Kierzkowski et al, 2011Kierzkowski et al, , 2013Marracci et al, 2011). Also, studies that address ecological and habitat features have provided interesting results.…”
Section: Discussionmentioning
confidence: 99%
“…Delimiting valid morphological characteristics to discriminate parental species and hybrid forms is, however, rather challenging. The green frog complex is undoubtedly very variable from a morphological and a genetic point of view (Kierzkowski et al, 2011;Hauswaldt et al, 2012). Recent papers have shown that the L (= lessonae) haplotype has a greater influence on morphology than the R (= ridibundus) haplotype, all the hybrid individuals being morphologically more similar to P. lessonae than to P. ridibundus (Kierzkowski et al, 2011(Kierzkowski et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial crosses and rearing of progeny were done according to standard protocol for water frogs (Berger et al 1994). Taxonomic identity of individuals was determined by morphology (Berger 1983, Plötner 2005, Kierzkowski et al 2011) and at least one of the following methods: actinomycin D (AMD)-DAPI staining (Schweitzer 1976, Heppich et al 1982, Ogielska et al 2004), LDH electrophoresis and 17 microsatellite loci (both methods described in Hauswaldt et al 2012). …”
Section: Methodsmentioning
confidence: 99%